An experimental study on harmful pollution reduction technique in low heat rejection engine fuelled with blends of pre-heated linseed oil and nano additive. (10th February 2021) - Elumalai, P.V.; Balasubramanian, Dhinesh; Parthasarathy, M.; Pradeepkumar, A.R.; Mohamed Iqbal, S.; Jayakar, J.; Nambiraj, M.
Abstract: The number of energy users in the world is growing more significant and more prominent in the current scenario for the automotive sector. About 70% of India's energy depends heavily on non-renewable fossil fuels. The cost and demand for the fuel are incredibly high. Over and above these reasons, environmental pollution is causing great concern. Consequently, many of the present researchers are focusing on finding a renewable fuel that can become an alternative for fossil fuel that is fast depleting. Biodiesels have drawn much attention from the research community because of their natural characteristics and chemical composition. In this manuscript, we have reported the linseed oil, which is effectively used as biodiesel (B20) and pre-heated to decrease the viscosity of the fuel with the aid of heater up to 100°C. The nanoparticle used in this work is titanium dioxide because of its highest oxygen content and easy availability in the market. Different proportions of titanium dioxide nanoparticles are blended (50 ppm, 100 ppm, 150 ppm, and 200 ppm) with pre-heated linseed oil in a coated diesel engine. The coating material used is Partially Stabilized Zirconium and the preferred thickness of 0.5 mm that is achieved with plasma spray techniques guidance. The crown of the piston or the top surface of the piston is coated with Partially Stabilized Zirconium (PSZ). It is observed that pre-heated PLSNP200 linseed oil has shown the enhanced performance and lower emissions when correlated with all the other blends. Pre-heating of Linseed oil and diesel engine (DI) coating has resulted in a 5.2% increase in thermal efficiency. The combination of PLSNP 200 reduces emissions of CO, smoke, and HC by 37.78%, 25%, and 37.92%, respectively. The oxides of nitrogen are elevated drastically by 7.43% when correlated with diesel fuel. The blend PLSNP200 increased the BTE and NOx by 8.11% and 6.53% respectively when compared with PLS20. The PLSNP200 blend HC, CO and Smoke opacity emission is drastically decreased by 33.82 21.05% and 26.57% when compared with the preheated linseed oil B20 (PLS20). Graphical abstract: Image 1